Security Planning Identification Model in E-Business - Muhammad Rifki Damanik; Musdiansyah Putra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
E-Business as an entity that is able to generate profits for organizations / companies and individuals is a valuable asset that must be maintained and protected. In the process of maintaining this, it is not easy because there are many obstacles and problems that must be faced. Various problems that threaten the security of e-Business need to be identified so that in the future the system can ward off these threats. The identification process as the first layer or the initial stage of the stages of security management in e-Business, is very important to do because the next stage is the risk evaluation process, the results depend on the findings that have been identified from this stage. The approach taken in designing a security planning identification model is through a literature study related to the e-Business security management process. The expected results from the formulation are in the form of recommendations for what processes need to be carried out in identifying security plans in e-Business..